Transformation Directions of the Financial Policy in the Process of Stabilisation of the Ukrainian Economy - Petrushevska Viktoriya V. (Bìznes Inform, 2013)
The goal of the article is consideration of theoretical provisions with respect to the state financial policy. The article considers the role of the financial policy in ensuring stabilisation of the Ukrainian financial system. It presents conceptual provisions regarding main goals, mechanisms and instruments of the stabilisation financial policy of the state. It develops economic indicators of its efficiency. The use of indicators of economic efficiency of the stabilisation financial policy by the bodies of state authority in their practical activity would provide the society with a possibility to assess expediency of measures of this policy increasing its efficiency and decreasing criticism at the government. A necessary direction of achievement of effectiveness and efficiency of the stabilisation financial policy is taking into consideration interests of all social groups (population, entrepreneurs, financial institutes and companies, etc.) by the bodies of state authority in the process of its development and realisation.